Cell saver does not increase pro-inflammatory cytokine levels and expression of adhesive molecules in the salvaged blood of patients undergoing off-pump coronary artery bypass surgery - Lin, Tzu-Yu; Chen, Yun; Chiu, Kuan-Ming; Lu, Cheng-Wei; Jean, Wei-Horng; Horng, Feng-Ming; Chu, Shu-Hsun (Acta anaesthesiologica Taiwanica, 2005)
Autotransfusion has been developed to avoid the risks of contaminating with infectious diseases and susceptivity to other complications of allogeneic blood transfusion. Previous studies have shown significant pro-inflammatory cytokine release and complement activation during blood salvage with cell saver (CS) in the course of on-pump coronary artery bypass grafting (CABG) surgery. Because both extracorporeal pump and CS machine are possible to induce the adverse cytokines release, thus, in this study, we investigated the influence of CS alone on the levels of pro-inflammatory cytokines and the expression of leukocyte surface antigens in patients undergoing off-pump CABG. Thirty patients proposed to undergo off-pump CABG were enrolled in this study. Five perioperative blood samples (peripheral blood before operation, blood in pericardial sac at operation, blood in the cell saver container, blood in the blood bag before transfusion, and peripheral blood one hour after operation) were obtained from each patient. The expression of activated leukocyte adhesive molecules (CD11b and CD18) and cytokine-inducible leukocyte-endothelial adhesive molecule (CD62P) were studied by flow cytometry. Enzyme-linked immunosorbent assay (ELISA) was conducted to determine the levels of pro-inflammatory cytokines including tumor necrosis factor-alpha (TNF-alpha), interleukin 6 (IL-6) and IL-8. All blood samples except the one obtained one hour after operation showed no difference of the expression of CD11b, and CD62P and the levels of TNF-alpha, IL-6 and IL-8 (P> 0.05). However, the expression of CD18 was decreased during the course of blood salvage. The peripheral blood obtained one hour after operation had significantly higher expression of the three tested leukocyte surface antigens and higher levels of three studied cytokines (P < 0.05). Our investigation indicated that the blood processing in cell saver alone did not increase the expression of either CD11b, CD18, or CD62P, and the levels of TNF-alpha, IL-6 and IL-8. The results suggest that cell saver seems not to significantly activate the leukocytes or cause inflammatory responses in the salvaged blood.